ANALYSIS OF INCOME AND BUSINESS FEASIBILITY OF SPOTTED SHRIMPCRACKERS (METAPENAEUS LYSIANASSA) "MITHA" IN HANDIL TERUSAN VILLAGE, ANGGANA DISTRICT, KUTAI KARTANEGARA REGENCY (Jurnal Pembangunan Perikanan dan Agribisnis, 2026)
This research aims to analyze the business feasibility of producing spotted shrimp crackers (Metapenaeus lysianassa) in Handil Terusan Village, Anggana District, Kutai Kartanegara Regency. The study utilizes a descriptive quantitative method with a case study approach involving a single business actor. Data were collected through interviews, observation, and documentation, and subsequently analyzed using financial feasibility indicators such as production costs, revenues, profits, Revenue Cost Ratio (R/C), Break Even Point (BEP), and Payback Period (PP). Results indicate that the shrimp cracker enterprise generates a monthly profit of IDR 599,104 with an R/C ratio of 1.31, signifying that the business is economically viable. The break-even point is reached at a production volume of 13 packages per month at a unit price of IDR 26,678, and the estimated payback period is approximately 2.4 years. The marketing channels utilized consist of zero-level channels (direct sales to consumers) and one-level channels (through intermediaries). The main supporting factors for the business include product quality and the possession of the P-IRT (Home Industry Food Production Permit). Conversely, the main challenges faced are limited workforce and marketing constraints. Based on these findings, the business demonstrates potential for further development.